Problem-based learning (PBL) in sociolinguistics as a way of encouraging active learning - Engku Ibrahim, Engku Haliza (EDP Sciences, 2018)
The major concern of this paper is to advocate the integration of PBL strategies in classroom instruction as a way of promoting active learning. It is undoubted that the benefits of problem-based learning (PBL) are numerous. In the sciences, PBL has been well integrated in the curriculum. This research reports of an experience of integrating problembased learning in an introductory Sociolinguistics course for 60 undergraduates of a Bachelors of English programme through a semester that ran for 14 weeks. A focused group interview and questionnaire were used to find out the perceptions of the students undergoing the hybrid PBL course. The findings of this study reveal that students generally enjoyed the PBL approach and found that they had little choice but to become active learners. Some challenges faced by the learners were also highlighted. These findings have implications for the integration of PBL in the field of social sciences